Primary Systemic Amyloidosis Presenting as Macroglossia - Karthikeya Patil; V G Mahima; B Shivanand Bagewadi (Wolters Kluwer Medknow Publications, 2004)
Amyloidosis is a rare disease of unknown origin characterised by extracellular deposition of fibrillar proteinaceous substance called amyloid having common morphological, structural and staining properties but variable protein composition. Oral manifestations have been reported in 39% of patients with amyloidosis and it manifests frequently as macroglossia. A rare case of Primary Systemic Amyloidosis presenting as Macroglossia in a patient with no known antecedent or coexistent disease is being presented and discussed.